Vagaries of Desire: A Collection of Philosophical Essays - Airaksinen, Timo (Philosophy, Literature, and Politics, 2019)
In Vagaries of Desire, Timo Airaksinen develops a new philosophical account of desire understood as mental state that focuses on a desirable possible world. Literary and philosophical themes, including sexuality, are discussed in terms of their metaphoric and metonymic features. Readership: Advanced students and specialists in philosophy of mind, anyone who is interested in the application of rhetorical notions to literature and philosophy, students and specialist in sexual ethics.